1996
DOI: 10.1097/00005131-199607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Fractures of the Femur and Tibia: Treatment with Retrograde Femoral Nailing and Unreamed Tibial Nailing

Abstract: Between 1989 and 1995 a total of 47 patients with 50 fractures of the ipsilateral femoral and tibial shafts without significant articular involvement were treated at Tampa General Hospital. Within this group were 24 patients with 26 fractures who were treated with intramedullary fixation of both bones using a technique of retrograde insertion of a femoral nail and unreamed insertion of an interlocking tibial nail. Information concerning the injuries, treatments, and much of the follow-up was gleaned from a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 19 publications
5
54
0
9
Order By: Relevance
“…We documented in our article that there were 10 out of 60 patients with ligament injury to the knee and they were treated accordingly. All patients were monitored for clinical signs of fat embolism; however, none of the patients in this in this series presented with these.We agree that the best treatment option is intramedullary nailing of both fractures (femur and tibia) as has been reported previously [1,[4][5][6]. However, when faced with Bansal [2] Type 1 injury (which involves fractures of the shaft of both the femur and the tibia) in an environment poor in resources, one may consider a combined approach with intramedullary nailing of the femur and functional cast bracing for the tibial shaft fracture, as this provided similar and comparable results to intramedullary nailing of both the femur and the tibia in our study.…”
supporting
confidence: 86%
“…We documented in our article that there were 10 out of 60 patients with ligament injury to the knee and they were treated accordingly. All patients were monitored for clinical signs of fat embolism; however, none of the patients in this in this series presented with these.We agree that the best treatment option is intramedullary nailing of both fractures (femur and tibia) as has been reported previously [1,[4][5][6]. However, when faced with Bansal [2] Type 1 injury (which involves fractures of the shaft of both the femur and the tibia) in an environment poor in resources, one may consider a combined approach with intramedullary nailing of the femur and functional cast bracing for the tibial shaft fracture, as this provided similar and comparable results to intramedullary nailing of both the femur and the tibia in our study.…”
supporting
confidence: 86%
“…The simultaneous operative stabilization of ipsilateral femoral and tibial fractures with retrograde nailing of the femur and antegrade nailing of the tibia has previously been reported [10]. A single medial prepatellar incision allows ready access to the entry points for both the tibial and femoral nails (Figures 8a and 8b).…”
Section: Discussionmentioning
confidence: 94%
“…Three of these studies were found in both the PubMed and EMBASE databases [11,31,37]. Twenty-two studies [21,23,24,[31][32][33][34][35]38 [15, 17-19, 22, 25-30, 36, 40, 42, 48] were excluded because they included adults, and we were unable to separate the adult data from those of patients \18 years of age. Three papers [29,37,43] were excluded because they were review papers and not studies that included patient treatment and follow-up information.…”
Section: Methodsmentioning
confidence: 99%